Estudantes adolescentes recém-iniciados no candomblé: discursos de resistência, confrontos e embates - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This so-called research is a subversive walk based on decolonial studies that I intend to dialog to denounce the forms of oppression that the colonized imposes, subordinating and inferiorizing the colonized - the marginalized peoples. Thus, four Candomblecist students participate hand in hand, who returned to school in the metropolitan region of Goiânia, attending high school, after starting in this religion that resists racist and colonial attacks. Thus, in a decolonial perspective of Critical Discourse Analysis, my analysis of the reports of these students who denounce a series of violence suffered to the detriment of latent religious racism was supported not only in schools, but also in society and promoted by the coloniality of power. The purpose of this journey is to identify discourses of resistance present in the reports of these students and, finally, to denounce a reality of exclusion and violence that people from Traditional Communities of Terreiro suffer.
Adolescent students newly initiated in candomblé: resistance speeches, confronts and confights
Keywords: Análise Crítica do Discurso - Candomblé; Candomblé - Discurso de Resistência; Candomblé - Decolonialidade - Discurso de Resistência; LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA